2021
DOI: 10.1038/s41467-021-21810-3
|View full text |Cite
|
Sign up to set email alerts
|

Joint profiling of DNA and proteins in single cells to dissect genotype-phenotype associations in leukemia

Abstract: Studies of acute myeloid leukemia rely on DNA sequencing and immunophenotyping by flow cytometry as primary tools for disease characterization. However, leukemia tumor heterogeneity complicates integration of DNA variants and immunophenotypes from separate measurements. Here we introduce DAb-seq, a technology for simultaneous capture of DNA genotype and cell surface phenotype from single cells at high throughput, enabling direct profiling of proteogenomic states in tens of thousands of cells. To demonstrate th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 48 publications
1
53
0
Order By: Relevance
“…3 A ). To determine the site-specific efficiencies of each SPI1 edit, we single-cell genotyped HSPCs after electroporation with CAS9 and gRNAs ( Demaree et al, 2021 ). The majority (76%) of SPI1 exon four – targeted cells possessed either monoallelic or biallelic edits, and the frequency of cells with exon five edits was even higher, exceeding 97% ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3 A ). To determine the site-specific efficiencies of each SPI1 edit, we single-cell genotyped HSPCs after electroporation with CAS9 and gRNAs ( Demaree et al, 2021 ). The majority (76%) of SPI1 exon four – targeted cells possessed either monoallelic or biallelic edits, and the frequency of cells with exon five edits was even higher, exceeding 97% ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Read 1 and read 2 sequences were demultiplexed into barcode groups and valid cell barcode groups were discriminated from background barcode groups by identifying the inflection point of the barcode rank plot versus number of associated reads (the “knee method”). Reads from valid cell barcodes were processed as previously described 12 . Briefly, FASTQ files with valid reads were aligned to the hg19 build of the human genome reference using bowtie2 (v2.3.4.1), filtered (properly mapped, mapping quality > 2, primary alignment), sorted, and indexed with samtools (v1.8).…”
Section: Methodsmentioning
confidence: 99%
“…1 b,c) (“ Supplementary Protocol ”). The modular design is compatible with described single cell sequencing workflows, including scDNAseq 7 , scRNAseq 2 , Abseq 8 , multimodal analyses 9 12 , and genome wide knockout screens 13 15 . Moreover, the optimized structure generates compact barcodes that can be assembled in a fraction of the time and cost compared to existing methods.…”
Section: Introductionmentioning
confidence: 99%
“…Demaree et al simultaneously interrogated the genotype and immunophenotype of single blast cells in longitudinally collected samples of three patients with AML using DNA and Antibody sequencing (DAb-seq), with one patient representing pediatric AML [ 36 ]. By analyzing 49 DNA loci via targeted amplification and 23 protein markers with barcoded antibodies, the authors identified various proteogenomic patterns among the three patients.…”
Section: Pathobiology Uncovered By Single-cell Analysismentioning
confidence: 99%
“…In line with this, leukemia samples as well as lymphoma cells circulating in the peripheral blood were the subjects in hematology-focused projects of early days [ 26 , 27 ], with acute myeloid leukemia (AML) being the most frequently published oncohematological entity [ 28 ]. To date, SCS datasets have been generated for a wide range of blood cancers, including chronic myeloid leukemia [ 29 ], myeloproliferative neoplasms [ 30 , 31 ], myelodysplastic syndrome/acute myeloid leukemia [ 21 , 27 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], acute lymphoblastic leukemia (ALL) [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ], chronic lymphocytic leukemia [ 59 , 60 , 61 ], mantle cell lymphoma [ 61 , 62 , 63 ], follicular lymphoma [ 61 , 64 , 65 , 66 ], diffuse large B-cell lymphoma [ 61 ], multiple myeloma [ 26 , 67 ], Hodgkin lymphoma […”
Section: Introductionmentioning
confidence: 99%